Counterdramaturgy and black corporalities: another point of view on the notion of dramaturgy (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This article aims to problematize the concept of dramaturgy originally known and spread since Aristotle's writings in the book Poetics. As an idea of ​​counterdramaturgy, a notion that is immersed in a philosophical complexity of Afro-ancestral “knowledge and doings” was approached, since the concept of dramaturgy does not deal with the basic needs of Afro-Brazilian dances. As a theoretical-philosophical support, reflections of thinkers who make use of African, Afro-Brazilian and anti-colonial epistemologies were used. The thesis was defended that the organizational needs of black narratives and corporeities, presented from their afrodiasporic dances, are connected to the existential corpus sinuosity of thought and to the circularity of events. The methodological paths developed are part of a set of theoretical-practical actions on scenic presence and Afro-Brazilian corporalities on stage developed throughout his work as an artist-researcher.
Keywords: dramaturgy; Aristotle; aphrodiaspora; black dances; Elinga